Management Evaluation of the QALIWARNA Program, in Educational Institutions - UGEL 03 Breña - Aldo Fernando Rejas de la Peña, Eddy Ronald Diaz Salvatierra, Yrma Rosa Godoy Pereyra, Leonor Alcira Durand Espejo de Benites, Mónica Liliana Agüero Ynca, Elita Hoyos Muñoz (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Social programs are of great help in Peru, benefiting the neediest, especially in the return to school after covid19, this makes us reflect on the value of the management of the QALIWARNA program in the Educational Institutions of UGEL 03 Breña. The purpose of this program is to promote awareness and support for schoolchildren, developing adequate eating habits, which favors community intervention and co-responsibility. The study is basic qualitative approach, descriptive level of non-experimental design, information collected over a period, developed through in-depth interviews with the management of the QALIWARNA project, by levels and scope. questions. The opening provides information on the relationships between categories and subcategories in different dimensions. The collection of information took place in a specific period where the instrument was applied: semi-structured interview, which provided relevant information to the specialists. From the analysis of the results, we can draw an approximate conclusion that the management of the QALIWARNA program provides a high percentage of benefits in terms of planning, implementation, and evaluation to improve the quality of students in the UGEL 03 IE – Breña.